A Pilot Randomized Controlled Study of Dexlansoprazole MR-Based Triple Therapy for Helicobacter Pylori Infection. Issue 11 (March 2016) - Wu, Deng-Chyang; Kuo, Chao-Hung; Tsay, Feng-Woei; Hsu, Wen-Hung; Chen, Angela; Hsu, Ping-I
Abstract : Abstract: Dexlansoprazole MR is the R-enantiomer of lansoprazole that is delivered by a dual delayed release formulation. It is effective for symptom control of patients with gastroesophageal reflux disease. However, its efficacy in the treatment of Helicobacter pylori infection remains unclear. This pilot, randomized, controlled, head-to-head study was conducted to investigate whether the efficacy of single-dose dexlansoprazole MR-based triple therapy was noninferior to double-dose rabeprazole-based triple therapy in the treatment of H pylori infection. Consecutive H pylori -infected subjects were randomly allocated to either 7-day dexlansoprazole MR-based standard triple therapy (dexlansoprazole MR 60 mg once daily, clarithromycin 500 mg twice daily, and amoxicillin 1 g twice daily) or rabeprazole-based triple therapy (rabeprazole 20 mg twice daily, clarithromycin 500 mg twice daily, and amoxicillin 1 g twice daily). H pylori status was assessed 6 weeks after the end of treatment. A total of 177 H pylori -infected patients were randomized to receive dexlansoprazole MR-based (n = 90) or rabeprazole-based (n = 87) triple therapy. Intention-to-treat analysis demonstrated no differences between eradication rates of the 2 study groups (83.3% vs 81.6%; P = 0.736). Per-protocol analysis yielded comparable results (85.1% vs 81.2%; P = 0.497). Both groups exhibited similar frequencies of adverse events (7.8% vs 4.6%; P = 0.536) and drug compliance (98.9% vs 97.7%; P = 0.496). Multivariate analysis disclosed that the presence of clarithromycin resistance was the only independent factors predictive of treatment failure with an odds ratio of 6.8 (95% confidence interval: 1.2–37.6). This work demonstrates that single-dose dexlansoprazole MR-based triple therapy yields a similar eradication rate as double-dose rabeprazole-based therapy. Since the pharmaceutical cost of the single-dose dexlansoprazole MR regime is lower than that of the double-dose rabeprazole regimen, dexlansoprazole-based therapy can reasonably be recommended in the first-line treatment of H pylori infection.